2005
DOI: 10.1002/ar.b.20076
|View full text |Cite
|
Sign up to set email alerts
|

Novel threadlike structures (Bonghan ducts) inside lymphatic vessels of rabbits visualized with a Janus Green B staining method

Abstract: A staining method has been developed for in situ and in vivo observation of a threadlike tissue afloat inside the lymphatic vessels of rabbits without adherence to the vessel wall. The existence of this novel structure was not noticed previously because it is extremely difficult to detect it by microscopic inspection of lymphatic vessels. We have found a method that utilizes Janus Green B (JGB), which stained heavily the novel structure. The tissue was studied by confocal laser scanning microscopy (CLSM), ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 10 publications
(25 reference statements)
2
72
0
1
Order By: Relevance
“…Elements of the intravascular HAR-ND are invisible without staining because typically they are very thin and transparent. The diameter of the intralymphatic HAR-NDS was 15-20 times smaller than the diameter of the surrounding lymphatic vessels [15]. The HAR-NDS diameter became artificially enlarged when alcian blue was injected (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Elements of the intravascular HAR-ND are invisible without staining because typically they are very thin and transparent. The diameter of the intralymphatic HAR-NDS was 15-20 times smaller than the diameter of the surrounding lymphatic vessels [15]. The HAR-NDS diameter became artificially enlarged when alcian blue was injected (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…We recently described a hyaluronic acid-rich node and duct system (HAR-NDS) [11,12] also known as the Bonghan (or Primo) vascular system [13][14][15][16]. We referred to the nodes and ducts as hyaluronic acid-rich node and hyaluronic acid-rich duct, respectively, and to the two together as hyaluronic acid-rich node(s) and duct(s) (HAR-ND) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The PVS floating in the lymph ducts has been extensively studied in rabbits [12] , rats [13] , and mice [14] . The lymph PVS is visible in vivo and in situ with suitable staining dyes like Alcian blue [15] and fluorescent nanoparticles [13] .…”
Section: Reviewmentioning
confidence: 99%
“…31 Tenderness has been one of the clearest physiological characteristics of acupuncture points since ancient medical literature. Our previous survey also clearly demonstrated that tender points and palpable bands, as well as formal acupuncture points, were used in clinical treatment by well trained Japanese acupuncturists.…”
Section: Close Relationship Between Acupuncture Points and Trigger Pomentioning
confidence: 99%